Inokulasi Fungi Mikoriza Arbuskula dan Dosis Pupuk Kandang terhadap Pertumbuhan dan Hasil Tomat (Lycopersicum esculentum Mill) - Darlina Darlina; Rosmaiti Rosmaiti; Syamsul Bahri (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Tomato (lycopersicum esculentum Mill) are a source of vitamins and minerals and have health benefits such as maintaining heart health. The denabd for tomatoes in indonesia continues to increase so it is necessary to take action to increase production by utilizing Fungi Mycorrhizal Arbuscular and manure. FMA is a fungus associated with plants where FMA binds nutrients in the soil. The aim of this research was to determine the effect of gungus mycorrhizal arbuscular and manure. This research was carried out in july – september 2023 in Siderejo village, Langsa Lama District, Langsa City. The research used a 2 factorial Randomized Block Design (RAK) with 3 replications. The first factor is the FMA dose, namely: F0 : 0 gr/plot, F1 : 20 gr/plot, F2 : 40 gr/plot, F3 : 60 gr/plot. The second factor is the dose of fertilizer P1 : 2,08 kg/plot, P2 : 5,6 kg/plot, P3 : 8,4 kg/plot. Date were analyzed using variance (F test) at the 5% and 1% levels. If the treatment has a real effect, continue with the BNJ test at the 5% level.